PELESTARIAN GULA CAKAR SEBAGAI BAHAN PEMANIS TRADISIONAL KHAS MAJALENGKA - Rani Amalani; Ade Juwaedah; Sudewi Yogha (Bogor Hospitality Journal, 2022)
Claw sugar is a processed food from white sugar which is traditionally used by the people of Majalengka as a drink sweetener. Claw sugar is the main ingredient of granulated sugar, until now granulated sugar can still be found in the market. The existence of this sugar claw is passed down from generation to generation orally or Informal Learning, not many have done transcription or writing. It is feared that this traditional food, which is a culture of an ethnic group, will become extinct by looking at the times that are growing rapidly. The research method used is a qualitative approach. The research source is the primary data source. The research design used is descriptive qualitative. In this study using the method of observation, interviews, and documentation. The results show that the origin of this claw sugar is said to have been first discovered by the Chinese in the 1920s. Claw sugar production in Majalengka, in fact there is a historical interrelationship with the existence of two sugar factories inherited from the Dutch colonial era in Majalengka, namely the Kadipaten Sugar Factory (PG) and PG Jatiwangi. One of the claw sugar factory businesses that still exists today is in the village of Tonjong which is owned by Mr. TS. This factory not only fulfills the sugar needs of the surrounding community, but also becomes one of the suppliers of sugar in traditional markets and minimarkets. This claw sugar is made from ingredients consisting of granulated sugar, food coloring, baking soda and water. Making claw sugar by boiling a mixture of sugar and water, after boiling add food coloring, and finally baking soda. After the mixture is poured into the mold, then let it cool, after it has cooled it is cut using a serrated knife and is ready to be marketed.